Kant be Compared: People High in Social Comparison Orientation Make Fewer—Not More—Deontological Decisions in Sacrificial Dilemmas. Issue 6 (August 2021) - Fleischmann, Alexandra; Lammers, Joris; Conway, Paul; Galinsky, Adam D.
The current work tests whether the dispositional tendency to compare oneself to others—social comparison orientation (SCO)—impacts decisions in moral dilemmas. Past research offers two competing predictions for how SCO impacts moral decision making: (a) SCO increases deontological judgments because people high in SCO care especially about social norms versus (b) SCO decreases deontological judgments because people high in SCO are competitive and thus unconcerned about causing harm to others. Four studies (two preregistered) find consistent support that SCO decreases deontological decisions. This relationship was robust in employing conventional (Study 1) and process dissociation (Studies 2–4) dilemma analytic techniques. Furthermore, we find that psychopathy uniquely mediates decreased deontological decisions among people high in SCO (Study 4). These results indicate that high-SCO people make fewer deontological decisions because they are less concerned with causing harm. Overall, the current research suggests that there is a dark side to making social comparisons.